Matrix Stiffness Corresponding to Strictured Bowel Induces a Fibrogenic Response in Human Colonic Fibroblasts - Johnson, Laura A. (2013)
BACKGROUND: Crohn’s disease is characterized by repeated cycles of inflammation and mucosal healing which ultimately progress to intestinal fibrosis. This inexorable progression towards fibrosis suggests that fibrosis becomes inflammation-independent and auto-propagative. We hypothesized that matrix stiffness regulates this auto-propagation of intestinal fibrosis. METHODS: The stiffness of fresh ex vivo samples from normal human small intestine, Crohn’s disease strictures, and the unaffected margin were measured with a microelastometer. Normal human colonic fibroblasts were cultured on physiologically normal or pathologically stiff matrices corresponding to the physiological stiffness of normal or fibrotic bowel. Cellular response was assayed for changes in cell morphology, α-smooth muscle actin (αSMA) staining, and gene expression. RESULTS: Microelastometer measurements revealed a significant increase in colonic tissue stiffness between normal human colon and Crohn’s strictures as well as between the stricture and adjacent tissue margin. In Ccd-18co cells grown on stiff matrices corresponding to Crohn’s strictures, cellular proliferation increased. Pathologic stiffness induced a marked change in cell morphology and increased αSMA protein expression. Growth on a stiff matrix induced fibrogenic gene expression, decreased matrix metalloproteinase and pro-inflammatory gene expression, and was associated with nuclear localization of the transcriptional cofactor MRTF-A. CONCLUSIONS: Matrix stiffness, representative of the pathological stiffness of Crohn’s strictures, activates human colonic fibroblasts to a fibrogenic phenotype. Matrix stiffness affects multiple pathways suggesting the mechanical properties of the cellular environment are critical to fibroblast function and may contribute to autopropagation of intestinal fibrosis in the absence of inflammation, thereby contributing to the intractable intestinal fibrosis characteristic of Crohn’s disease.